The Robust Model Predictive Control Design for Linear Interconnected Systems - Afifah, Nida Nur; Solikhatun, S. (Jurnal ILMU DASAR, 2023)
In this paper, we discuss the design of robust model predictive control for linear interconnected systems by several constraints. Linear interconnected system is a complex systems which consist of several subsystems and the dynamic of subsystem is influenced by the states or outputs of the other subsystems. The systems are controlled by formulating and applying the model predictive control on each subsystems. We formulate the optimization problem that minimize the cost function for each subsystems. The optimization problem is solved by gradient method to get the minimum cost function. Numerical simulation was conducted to show the effectiveness and performance of robust model predictive control. Based on the results of the numerical simulation and test the robustness, it can be shown that the robust model predictive control is effective to control the linear interconnected systems.